Another piece in the pirfenidone puzzle. Issue 4 (27th April 2023) - Lehmann, Mareike; Kolb, Martin
Clinical studies and real-world experience show that pirfenidone is effective in decelerating disease progression in idiopathic pulmonary fibrosis (IPF) patients. However, many of the details that define its molecular mechanisms are still unknown. Yes, it works, but how exactly? And why should we care? Identifying the missing pieces and completing the puzzle will be helpful for the development of more specific and hopefully better therapeutics, and instrumental in developing effective combination therapies that have a better safety profile while simultaneously allowing for disease progression to be halted, or perhaps even an improvement in lung function. An editorial discussing the recent article by Ma and co-workers that contributes another puzzle piece to the mechanism of action for pirfenidone with elegant in vitro and in situ studies, and importantly, using a clinically relevant drug concentration https://bit.ly/40Vi0zr